A classification of reliable multicast protocols. - Atwood, J.W (IEEE Network : the magazine of global information exchange)
The range of user requirements on multicast protocols is so wide that no single protocol will ever satisfy them. The set of multicast protocols can be classified using the user requirements, and the architectures, mechanisms, communications patterns, and policies used to satisfy these requirements. We provide such a classification, and illustrate it with several example protocols chosen to cover the range of features described.